Aging, estrogen loss and epoxyeicosatrienoic acids (EETs). - Alison R Lee (Public Library of Science (PLoS), 2013)
Inflammation is a key element in many cardiovascular diseases. Both estrogen loss, caused by menopause, and aging have inflammatory consequences. Epoxyeicosatrienoic acids (EETs) are anti-inflammatory molecules synthesized by various cytochrome P450 (Cyp) enzymes from arachidonic acid. EETs are in the third (Cytochrome P450) pathway of arachindonic acid metabolism, others being cyclooxygenases and lipoxygenases. We hypothesized that aging and estrogen loss would reduce levels of anti-inflammatory EETs. Adult (6 mo) and aged (22 mo) ovariectomized rats with (OP) and without (Ovx) 17-∃-estradiol replacement were used in this study. Mass spectrometry was used to measure levels of EETs and their metabolites, dihydroxyeicosatrienoic acids (DHETs). Levels of Cyp2C2, Cyp2C6, and Cyp2J2, the principal Cyps responsible for EETs synthesis, as well as soluble epoxide hydrolase (sEH), which metabolizes EETS to DHETs, were determined via western blot. Overall Cyp levels decreased with age, though Cyp2C6 increased in the liver. sEH was increased in the kidney with estrogen replacement. Despite protein changes, no differences were measured in plasma or aortic tissue levels of EETs. However, plasma 14,15 DHET was increased in aged Ovx, and 5,6 DHET in adult OP. In conclusion neither aging nor estrogen loss decreased the anti-inflammatory EETs in the cardiovascular system.